The Effectiveness of the Hybrid Learning Materials with the Application of Problem Based Learning Model (Hybryd-PBL) to Improve Learning Outcomes during the COVID-19 Pandemic - Thamrin Thamrin; Saidun Hutasuhut; Reza Aditia; Fauziyah Riyan Putri (IJORER : International Journal of Recent Educational Research, 2022)
Study aimed to see the effectiveness of the hybrid learning materials application with Problem based learning (PBL) model to improve students’ outcome in evaluation course in learning outcomes at the Business Education Study Program, State University of Medan. The study used a quasi-experimental method of the Posttest control group design. Data collection was carried out by conducting tests after class. The sample selected in this study were all students of the Business Education study program in evaluation course in learning outcomes. The results showed that the application of hybrid learning with the PBL model was effective to improve learning outcomes in evaluation course in learning outcomes . The results of this study also found that the independence and creativity of student learning was higher by applying hybrid learning with problem-based learning models compared to the control class. The results of this study contributed to the lecturers' evaluation of learning outcomes in improving the quality of learning, which has been traditional, by applying hybrid learning teaching materials with problem-based learning models, especially during the current Covid 19 pandemic and to answer the demands of learning in the industrial revolution era. 4.0.